1977
DOI: 10.1111/j.1399-3054.1977.tb01525.x
|View full text |Cite
|
Sign up to set email alerts
|

Improved Growth of Tissue Cultures of the Onion, Allium cepa

Abstract: A forty‐fold increase in tissue fresh weight has been achieved for Allium cepa stem tissue callus grown on a modified B5 medium with increased ammonium, phosphate and nitrogen levels; and decreased level of 2,4‐dichlorophenoxyacetic acid. Growth was examined on several standard media, using fresh weight, dry weight and cell number as parameters over an 8‐week growth period. Further, tissue grown upon this medium is more friable than on other media. The value of such friable callus for suspension culture initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0
4

Year Published

1991
1991
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(63 citation statements)
references
References 11 publications
1
53
0
4
Order By: Relevance
“…Novak (1990) noted that B5 (Gamborg et al 1968)-based media have been in common use for Allium tissue cultures. Dunstan & Short (1977) obtained a substantial increase in A. cepa callus growth rate after increasing the ammonium, phosphate and nitrate levels of the B5 medium. Their so-called BDS medium has served as the basal medium in a number of subsequent studies (Phillips & Luteyn 1983;Phillips & Hubstenberger 1987;Lu et al 1989), Somatic embryogenesis has been observed in callus cultures of A. cepa (Dunstan & Short 1977;Phillips & Luteyn 1983); A. fistulosum (Phillips & Hubstenberger 1987;Shahin & Kaneko 1986) and in F1 hybrids between A. cepa and A. fistulosum (Shahin & Kaneko 1986;Phillips & Hubstenberger 1987;Lu et al 1989).…”
Section: Introductionmentioning
confidence: 98%
“…Novak (1990) noted that B5 (Gamborg et al 1968)-based media have been in common use for Allium tissue cultures. Dunstan & Short (1977) obtained a substantial increase in A. cepa callus growth rate after increasing the ammonium, phosphate and nitrate levels of the B5 medium. Their so-called BDS medium has served as the basal medium in a number of subsequent studies (Phillips & Luteyn 1983;Phillips & Hubstenberger 1987;Lu et al 1989), Somatic embryogenesis has been observed in callus cultures of A. cepa (Dunstan & Short 1977;Phillips & Luteyn 1983); A. fistulosum (Phillips & Hubstenberger 1987;Shahin & Kaneko 1986) and in F1 hybrids between A. cepa and A. fistulosum (Shahin & Kaneko 1986;Phillips & Hubstenberger 1987;Lu et al 1989).…”
Section: Introductionmentioning
confidence: 98%
“…Podem-se encontrar vários meios para tal finalidade, como MS (Murashige & Skoog, 1962), WPM [(Wood Plant Medium) Lloyd & McCown (1980)], MSM (meio MS modificado por Monteiro-Hara, 2000), BDS (Dunstan & Short, 1977) e o meio DSD1 (Silva & Doazan, 1995).…”
Section: Introductionunclassified
“…On the other hand, Luciani et al (2006) tested different explants for micropropagation of variety 069, which were cultivated on BDS medium (Dustan & Short, 1977), supplemented with picloram, 2,4-D and BA. The basal plates and meristems resulted in the highest values of shoot regeneration, and 2,4-D proved to be better than picloram for inducing callus and shoot formation.…”
Section: Organogenesismentioning
confidence: 99%